Insight into students' perception of teaching : case of economic higher education institution - Arbula Blecich, Andrea (Array, 2019)
The aim of this paper is to analyse students’ perceptions of teaching from three different perspectives: students’ interest, teacher and course assessment. We use ordinal logistic model to quantify the effects of grade, pass rate and class size on results of evaluation of undergraduate and graduate courses held during the summer and winter semesters in the academic year 2016/2017. The data were collected using a standardised online questionnaire. Research results indicate that on the observed economic HEI, both teacher and course assessment is positively and significantly affected by student’s achieved grade, and by class size. Moreover, we find large and significant difference between students’ interest in study programmes delivered in Croatian and those delivered in English. Students enrolled in English study programme value pass rate over grade, as opposed to students enrolled in Croatian study programme. We attribute this to the different motivation of students, that is, students enrolled in English programme are more prone to participation in student mobility programmes.